TANGGUNG JAWAB NOTARIS TERHADAP PENYIMPANAN MINUTA AKTA SEBAGAI NOTARIS PROFESIONAL: Tanggung Jawab Notaris terhadap Penyimpanan Minuta Akta sebagai Notaris Profesional - Syamsu, Fauzan (UIR Press, 2025)
This research discusses the responsibility of a notary in keeping minutes of deeds as part of the notary's protocol. As a public official as regulated in Law Number 02 of 2014 concerning the Position of Notaries, Notaries have a legal obligation to keep minutes which are original documents of authentic deeds. Deed minutes play an important role in the legal evidence system, because this deed is a valid piece of authentic evidence. In its implementation, the Notary is obliged to maintain the security, confidentiality and authenticity of the minutes of the deed so that no damage or loss occurs which could have a negative impact on interested parties. This research uses normative juridical methods with literature studies and qualitative analysis to examine the laws and regulations governing the responsibilities of Notaries. The discussion includes the Notary's obligations in maintaining minutes of deeds, procedures for safe storage, as well as sanctions given if violations occur. The conclusion of this research is that mandatory recording by a Notary is not only a legal obligation, but is also a form of protection of the community's legal rights.